Hubungan Religiositas dan Motivasi dengan Prestasi Belajar Pendidikan Agama Islam Siswa - M. Danial Rahman; Muhammad Syarifuddin Rahman (ALSYS, 2026)
Religiosity and learning motivation are important factors that have the potential to support students’ learning achievement, particularly in Islamic Religious Education subjects. This study aims to analyze the profile of students’ religiosity, learning motivation, and learning achievement; the relationship between religiosity and learning achievement; the relationship between learning motivation and learning achievement; and the simultaneous relationship between religiosity and learning motivation and students’ Islamic Religious Education learning achievement at MAN 1 Konawe. This study employed a quantitative approach with a survey method and correlational design. The research population included all 340 students of MAN 1 Konawe, while a sample of 77 students was determined through stratified random sampling using the Yamane formula. Data were collected through a questionnaire that had been tested for validity and reliability. Data analysis was conducted descriptively and inferentially after meeting the prerequisite tests, including normality, linearity, multicollinearity, and autocorrelation tests. Hypothesis testing was carried out using correlation analysis and multiple regression. The results show that students’ religiosity, learning motivation, and learning achievement are in the moderately good category. Religiosity has a positive and significant relationship with learning achievement, and learning motivation also has a positive and significant relationship with learning achievement. Simultaneously, religiosity and learning motivation have a positive and significant relationship with students’ Islamic Religious Education learning achievement at MAN 1 Konawe. These two variables contribute 62.3%, while the remaining 37.7% is influenced by other factors outside this study. The conclusion of the study emphasizes that the better students’ religiosity and learning motivation, the better the Islamic Religious Education learning achievement they attain. These findings imply the importance of strengthening religious values and learning motivation in the educational process to support the improvement of students’ academic achievement.